High Frequency of Post-Transfusion Microchimerism Among Multi-Transfused Beta-Thalassemic Patients - Matsagos, Spyridon; Verigou, Evgenia; Kourakli, Alexandra; Alexis, Spyridon; Vrakas, Spyridon; Argyropoulou, Constantina; Lazaris, Vasileios; Spyropoulou, Panagiota; Labropoulou, Vasiliki; Georgara, Nicoletta; Lykouresi, Maria; Karakantza, Marina; et al. (Frontiers in Medicine, 2022)
Background: Transfusion-Associated Microchimerism implies the presence of allogeneic hematopoietic cells in an individual, following the transfusion of a blood product. It is a transfusion-related adverse effect / long term consequence, which has not been well-investigated among regularly transfused patients with thalassemia. Patients and methods: We investigated 64 regularly transfused, homozygous β-thalassemic patients and 21 never-transfused healthy volunteer blood donors (controls) for the presence of microchimerism in their sera, using Real-time PCR targeting circulating allogeneic, both, HLA-DR and non-HLA alleles. Investigation was longitudinally repeated in patient subsets for more than 2 years. Results were correlated with clinical and laboratory parameters, peripheral blood lymphocyte immunophenotype, blood storage time and donor’s gender, to identify potential contributing factors for microchimerism generation. Results: Overall, microchimerism was detected in 51/64 patients (79.6%) and in 6/21 controls (28.5%, p=0.0001). Forty-three patients (67.2%) exhibited long-term microchimerism (persisted for more than 6 months), confirmed at all time-points investigated. Microchimerism was more frequent among elderly, female, splenectomized, and more heavily transfused patients, as well as among those, exhibiting higher serum ferritin levels. In these patients a distinct descending pattern of CD16dim+CD56dim+ NK-cells (p<0.001) and an ascending pattern of CD4+CD25brightCD127- regulatory T-cells (p=0.022) for increasing allelic burden were noticed, suggesting the establishment of recipient immune tolerance against the donor-derived chimeric alleles. Both, splenectomized and non-splenectomized thalassemic patients exhibited the same trend. The storage time of transfused blood products and donor/gender mismatch had no impact on the development of microchimerism. Discussion-conclusive remarks: Transfusion-associated microchimerism appears to be a very common complication among multi-transfused thalassemic patients. The potential clinical consequences of this phenomenon remain as yet unclear. Immune tolerance attributed to disease itself and to repeated transfusions might at least in part explain its appearance.